LOGISTIC DEVELOPMENT, SUPPLY CHAIN MANAGEMENT ON SALES GROWTH - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The research focused on topic logistic development, supply chain and sales growth with e aims of examine the relationship between logistic development, supply chain and sales growth.The objective were to examine the relationship between logistic development and sales growth , to examine the relationship  between   supply chain and  sales growth  and to study the factor structure of logistic development, supply chain and  sales growthData was collected through questionnaires and interviews with SSUWC workers owners in Jonglei state who were purposively selected and used as sample in the study.The findings disclosed that management function of municipality is moderated by its workers. The data outcomes have out shown that there is no significant difference on government and logistic function.It is recommended that management structures at municipality sector should make a drastic review of their human resource management practices especially on management parts. They need to develop human resources management strategies plans that cover the developmental aspect. There is needed to take into account what employees, customers’ value most in their work.